Derivatives As A Function
Derivatives As A Function
Definition The derivative of the function f (x) with respect to the variable x is the
function f 0 whose value at x is
f (x + h) − f (x)
f 0 (x) = lim
h→0 h
Notations
There are many ways to denote the derivative of a function y = f (x), where the in-
dependent variable is x and the dependent variable is y. Some common alternative notations
for the derivative are
dy df d
f 0 (x) = y 0 = = = f (x) = D(f )(x) = Dx f (x)
dx dx dx
x
Example 1.4.2 Differentiate f (x) =
x−1
1
√
Example 1.4.3 Differentiate f (x) = 5x − 8
df d
= (c) = 0
dx dx
Illustration:
a). f (x) = 1
1
b). y = −
8
√
c). f (x) = 3
2
1.4.2.2 Power Rule
d n
x = nxn−1 ,
dx
a) f (x) = x3
b) g(x) = x2/3
1
c) y =
x4
d) f (x) = x−4/3
√
e) f (x) = x2+π
3
1.4.2.3 Derivative Constant Multiple Rule
d du
(cu) = c
dx dx
.
d
(cxn ) = cnxn−1 .
dx
d
Example 1. 3x2 =
dx
d 5
Example 2. =
dx x2
d −7
Example 3. =
dx x−2/7
4
every point where u and v are both differentiable. At such points,
d du dv
(u + v) = +
dx dx dx
.
√ √
3 2
Example 3. Find f 0 (x) if f (x) = x + 9 x7 − √
5
x2
5
1.4.2.3 Derivative Product Rule
d dv du
(uv) = u + v .
dx dx dx
The derivative of the product uv is u times the derivative of v plus v times the
derivative of u. in prime notation, (uv)0 = uv 0 + vu0 . In function notation,
d
[f (x)g(x)] = f (x)g 0 (x) + g(x)f 0 (x).
dx
√
Example 2. Find the derivative of f (x) = x3 (2 x + x1/4
6
1.4.2.3 Derivative Quotient Rule
If u and v are differentiable at x and if v(x) 6= 0, then the quotient u/v is differen-
tiable at x, and
u du dv
− u dx
d u dx
=
dx v v2
t2 − 1
Example 1. Find the derivative of y =
t3 + 1
(x − 1)(x2 − 2x)
Example 2. Find the derivative of y =
x4
d n du
u = nun−1
dx dx
7
Example 1. Find the derivative of f (x) = (x3 − 2x + 3)3
p
Example 2. Find the derivative of y = (2x3 + 1)5
r
3 x−3
Example 2. Find the derivative of y =
x+3
8
Second- and Higher-Order Derivatives
If y = f (x) is differentiable function then its derivative f 0 (x) is also a function. If f 0 is also
differentiable, then we can differentiate f 0 to a get a new function of x denoted by f 00 . So
f 00 = (f 0 )0 . The function f 00 is called the second derivative of f because it is the derivative
of the first derivative. It is written in several ways:
d2 y dy 0
00 d dy
f (x) = 2 = = = y 00 = D2 (f )(x) = Dx2 f (x).
dx dx dx dx
dy 0 d
y 00 = = (6x5 ) = 30x4 .
dx dx
dy 00 d3 y
If y 00 is differentiable, its derivative, y 000 =
= 3 is the third derivative of y
dx dx ,
with respect to x. The name continue as we imagine, with
d (n−1) dn y
y (n) = y = n = Dn y
dx dx
denoting the nth derivative of y with respect to x for any positive integer n.
Example 2. Find all the derivatives of the function f defined by f (x) = 8x4 + 5x3 − x2 −
7x + 13
9
CHAIN RULE
dy dy du
= ·
dx du dx
dy u2 − 1 √
Example 1. Find , given y = 2 and u = 3 x2 + 2
dx u +1
dy √
Example 2. Find , given y = x3 − 3x + 5 and x = 12 t + 3.
dt
√ dy √
Example 3. If y = x2 − 4x and x = 2t2 + 1, find when t = 2
dt
10
IMPLICIT DIFFERENTIATION
Implicit Functions. An equation f (x, y) = 0, on perhaps certain restricted ranges of the
variables, is said to define y implicitly as a function of x.
1. Solve, when possible, for y and differentiate with respect to x. Except for very simple
equations. This procedure is to be avoided.
dy
Example 1. Find if y 2 = x
dx
√ √ dy
Example 2. x+ y = 4;
dx
dy
Example 3. 3x4 y 2 − 7xy 3 = 4 − 8y; find
dx
11
Exercises. Do as indicated.
A. Find the derivative by applying the appropriate rule of differentiation.
1. y = x5 + 5x4 − 10x2 + 6
1 4
3. y = 2
+√
2x x
√ √
4. y = 2x + 2 x
12
2 6
5. y = √ + √
3
t t
6. y = (1 − 5x)6
7. y = (3x − x3 + 1)4
8. g(x) = (3 + 4x − x2 )1/2
13
3r + 2
9. v =
2r + 3
5
x
10. f (s) =
1+x
√
11. v = 2x2 2 − x
√
12. f (x) = x 3 − 2x2
14
√
13. y = (x − 1) x2 − 2x + 2
x
14. y = √
1 − 4x2
√
q
15. y = 1+ x
r
x−1
16. f (x) =
x+1
15
17. y = (x2 + 3)4 (2x3 − 5)3
t2 + 2
18. y =
3 − t2
4
x3 − 1
19. y =
2x3 + 1
16
B. Find the first and the second derivative of the following functions
x3 + 7
20. y =
x
(θ − 1)(θ2 + θ + 1)
21. r =
θ3
1 + 3z
22. w = (3 − z)
3z
17
dy
C. Use Chain Rule to find .
dx
u−1 √
23. y = ,u = x
u+1
24. y = u3 + 4, u = x2 + 2x
√ √
25. y = 1 + u, u = x
√
26. y = u, u = v(3 − 2v), v = x2
18
dy
D. Find using implicit differentiation.
dx
27. x2 y − xy 2 = 6
28. 2xy + y 2 = x + y
29. x2 (x − y)2 = x2 − y 2
19
d2 y
E. Find using implicit differentiation.
dx2
30. x2 + y 2 = 1
d2 y
32. If x3 + y 3 = 16, find the value of at the point (2, 2).
dx2
20